2018
DOI: 10.1007/s12665-018-7547-7
|View full text |Cite
|
Sign up to set email alerts
|

Bowing of marble slabs: can the phenomenon be arrested and prevented by inorganic treatments?

Abstract: Bowing of thin marble slabs is a phenomenon affecting both historic monuments and modern buildings. In spite of the ubiquity and destructiveness of this phenomenon, no fully satisfactory treatment is currently available to arrest and/or prevent bowing. In this study, a treatment based on formation of hydroxyapatite (HAP) was investigated as a possible route to arrest and possibly prevent bowing of Carrara marble slabs. Four different formulations of the HAP-treatment were tested and compared to ammonium oxalat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 49 publications
4
46
1
Order By: Relevance
“…After treatment with "DAP", small new bands appeared at 602 and 561 cm −1 , which indicated the formation of new calcium phosphates [61]. The fact that these new bands were very small was due to the low concentration of DAP used for the treatment (0.1 M), which was consistent with a previous study where FT-IR bands of new calcium phosphates were found to be more pronounced for more concentrated DAP solutions [60]. To distinguish between formation of hydroxyapatite [HAP, Ca 10 (PO 4 ) 6 (OH) 2 ] and octacalcium phosphate [OCP, Ca 8 H 2 (PO 4 )6·5H 2 O], which both could be formed as the reaction product between calcareous stones and DAP solutions [51] and both have FT-IR bands at 560-563 and 600-602 cm −1 [61], the position of the other strong bands (at 1031 cm −1 for HAP and 1023 cm −1 for OCP [61]) should be considered.…”
Section: Composition Of the New Phasessupporting
confidence: 90%
See 1 more Smart Citation
“…After treatment with "DAP", small new bands appeared at 602 and 561 cm −1 , which indicated the formation of new calcium phosphates [61]. The fact that these new bands were very small was due to the low concentration of DAP used for the treatment (0.1 M), which was consistent with a previous study where FT-IR bands of new calcium phosphates were found to be more pronounced for more concentrated DAP solutions [60]. To distinguish between formation of hydroxyapatite [HAP, Ca 10 (PO 4 ) 6 (OH) 2 ] and octacalcium phosphate [OCP, Ca 8 H 2 (PO 4 )6·5H 2 O], which both could be formed as the reaction product between calcareous stones and DAP solutions [51] and both have FT-IR bands at 560-563 and 600-602 cm −1 [61], the position of the other strong bands (at 1031 cm −1 for HAP and 1023 cm −1 for OCP [61]) should be considered.…”
Section: Composition Of the New Phasessupporting
confidence: 90%
“…After treatment with "DAP", small clusters of the new calcium phosphates were visible on the stone surface, which, also in this case, was not continuously coated with the new phases. Generally, new calcium phosphates formed in carbonate stones from the reaction with ammonium phosphate solutions show a flower-like morphology [25], but, in the case of dilute solutions (such as that adopted in the present case), the formation of small clusters has been reported before [59,60].…”
Section: Morphology Of the New Phasesmentioning
confidence: 56%
“…Coatings formed at even higher DAP concentration (3 M DAP, followed by limewater application [ 42 ]) exhibited diffused cracking [ 43 ] but still a remarkable consolidating effectiveness. Because the consolidating action derives from the ability of the new CaP phases to seal the tips of cracks among grains (even though a discontinuous coating is formed), a steady increase in mechanical consolidation (assessed by ultrasound) was found for increasing DAP concentration, both in porous limestone [ 1 ] and in marble [ 44 ].…”
Section: Definition Of the Treatment Parametersmentioning
confidence: 99%
“…Application of a limewater poultice after treatment with a 3 M DAP solution has been investigated as well [ 42 , 43 , 44 , 45 , 49 , 50 , 51 ]. In this case, the limewater poultice, applied after treatment with the DAP solution and drying, has the twofold purpose of (i) providing additional calcium ions for the reaction with unreacted DAP and (ii) removing all the unreacted DAP during drying, as the poultice is left to dry in contact with the stone [ 42 ].…”
Section: Definition Of the Treatment Parametersmentioning
confidence: 99%
“…The use of consolidants improves the drainage of the water during the drying process and increases the durability of the materials (Molina et al 2018). The use of a treatment based on the formation of hydroxyapatite do not cause excessive pore occlusion and stiffening, and therefore enhances marble durability to thermal cycles and bowing (Sassoni et al 2018). Weathering crusts can have significant differences in hydric and thermal expansion in relation to the stone and the conservation treatment should promote the reduction of this heterogeneity (Wedekind et al 2018).…”
mentioning
confidence: 99%